Collaboration of Government, Academics, and Communication Through Collaborative Governance to Strengthen Regional Competitiveness - Wahyuni, Lilis; Musdiana, Andi Desy; Lastri, Novelma; Dewi, Ernita Puspa (Green Publisher Indonesia, 2025)
Competition between regions requires a collaborative strategy to increase long-term competitiveness. The main challenges lie in limited resources, separation of roles between actors, and lack of effective communication in regional development. This research aims to analyze how the government, academics, and other stakeholders can collaborate through a collaborative governance approach to strengthen regional competitiveness. The research method used is qualitative with data collection techniques through literature studies. Data analysis is carried out through data reduction, presentation, and conclusion drawn. The results of the study show that strengthening regional competitiveness cannot be achieved partially, but requires active involvement from the government as a provider of inclusive policies and a conducive ecosystem, academics as contributors to knowledge and innovation, and communication as a vision-binding and sustainability of collaboration. The conclusion of this study emphasizes that strengthening regional competitiveness can be realized through the implementation of transparent, participatory, and adaptive collaborative governance. The implications of this study emphasize the importance of building a transparent, participatory, and adaptive collaboration mechanism so that regional competitiveness can be improved continuously.